Comparison of Student Learning Activities between the Active Learning Strategy Type Everyone is a Teacher Here and the Type True or False in Class X of Mapat Tunggul Selatan High School - Khoirun Najmi Septiana; Lilis Suryani; Asep Asep (Jurnal Geografi, Lingkungan dan Kesehatan, 2026)
The purpose of this study was to compare student learning activities between the active learning strategy Everyone is a Teacher Here, and True or False type. This type of research is "Quasi Experiment Research" with a population of all students of SMAN Mapat Tunggul Selatan Academic Year 2025/2026. Purposive sampling was used, so that Class X phase E1 was selected as experimental class 1 and Class X phase E2 as experimental class 2. Data collection techniques were observation of learning activities, interviews, and documentation. While the data analysis technique was quantitative descriptive and t-test. Quantitative data analysis showed that the average learning activity of students in experimental class I was 82% (very active), while in experimental class II was 75% (active). The results of the t-test at a significance level of 0.05 obtained t count 0.446 while t table 1.67. Thus, there is no difference between the learning activities of students who use the active learning strategy type Everyone is a Teacher Here and the True or False type in the class of X.